A Journey of Transformation: A Model of Educators' Learning Experiences in Educational Technology - Kathleen P. King (Adult Education Research Conference, 2002)
Based on research among 205 educators, it is indicated that learning educational technology has the potential to deeply impact educators’ perspectives and practice. This paper extends the findings of previous work to provide a research-driven model of transformational learning to guide professional development in educational technology.